Galvanically isolated modular converter. Issue 12 (1st October 2016) - Christe, Alexandre; Dujic, Drazen
Abstract : Direct current (DC) electrical grids are already a reality in low voltage (LV) telecom distribution systems and point‐to‐point high voltage DC transmission. Medium voltage (MV) domain, despite its big potential, still suffers from a lack of suitable conversion and protection technologies. This study presents a bidirectional, galvanically isolated, high power converter for interface of emerging MVDC grids with readily available LVAC grids. To achieve high conversion efficiency, the integration of a line frequency transformer into the structure of the modular multilevel converter (MMC) is analysed and described in a systematic manner. Two configurations of the galvanically isolated modular converter: (i) interleaved and (ii) stacked, are derived and presented. Differences and similarities, compared to the classical MMC, are presented on the system design level, while control performances are evaluated by means of simulations.